Polyester, non-woven fabric and preparation method thereof

By adding monomers with specific structures to the polyester preparation, the problem of degradation of heat resistance after polyester modification is solved, and the thermal deformation temperature and heat resistance are improved while low melting point, which is suitable for the preparation of high-performance non-woven fabrics.

CN119570003AActive Publication Date: 2025-03-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311138743.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-05
Publication Date
2025-03-07
Estimated Expiration
2043-09-05

AI Technical Summary

Technical Problem

In the prior art, while the polyester modification reduces the melting point, it leads to a decrease in the glass transition temperature, thereby reducing the heat resistance.

Method used

In the process of polyester preparation, monomer having a specific structure, specifically, monomer having a structure represented by formula (I) and monomer having a structure represented by formula (II), esterification and polycondensation reaction are carried out to increase the thermal deformation temperature of the polyester.

Benefits of technology

It is achieved to significantly increase the thermal deformation temperature of the polyester while having a low melting point and improve the heat resistance, making the polyester suitable for the preparation of non-woven fabrics with good resilience and heat resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570003A_ABST
    Figure CN119570003A_ABST
Patent Text Reader

Abstract

The invention relates to the field of polymer chemical industry, and discloses polyester and a preparation method thereof. The melting point of the polyester is 158-205 DEG C, and the thermal deformation temperature of the polyester is 48-78 DEG C under the condition that the pressure is 0.45 MPa. The preparation method of the polyester comprises the following steps: (1) under an esterification reaction condition, mixing a binary acid monomer, a dihydric alcohol monomer, a modified monomer and a catalyst, and carrying out a first-stage reaction to obtain a prepolymer; the modified monomer contains a monomer with a structure as shown in a formula (I) and a monomer with a structure as shown in a formula (II); and (2) carrying out a second-stage reaction on the prepolymer under a polycondensation reaction condition. The polyester has the advantages of low melting point, high thermal deformation temperature and good heat resistance. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer chemical industry, and in particular to polyester, non-woven fabric and a preparation method thereof. Background Art

[0002] At present, the squeeze rollers of metal sheet and strip production lines in China are mostly made of rubber or polyurethane, which have the disadvantages of poor drying and cleaning effect, easy to slip, short service life, heat resistance, acid and alkali corrosion resistance, etc. There is a new type of non-woven fabric roller that can maintain close contact with the metal sheet and strip to obtain the best squeezing effect. The friction coefficient is 24 times that of the rubber roller or polyurethane roller, which can solve the problem of metal sheet and strip slipping. The non-woven fabric squeeze roller is composed of high-strength non-woven fabric and metal core shaft. The degreasing and pickling machines in the production of metal sheet and strip need squeeze rollers to carry out the sheet and strip squeezing process. The non-woven fabric squeeze roller needs good resilience and strength, so the material selection of non-woven fabric is crucial.

[0003] Polytrimethylene terephthalate (PTT) fiber has excellent elastic recovery and softness, excellent wrinkle resistance, sunlight resistance and dyeability, so it can be used as fabrics for high-end clothing, elastic swimsuits, underwear, interior decoration, carpets, etc. In addition to being used as fibers, PTT also has potential application value in non-woven fabrics, films, thermoplastic engineering plastics and mold products. As a raw material for producing PTT non-woven fabrics, low-melting-point PTT can be directly hot-rolled without additional compounding of other fibers or adding adhesives, which has the advantages of convenience, speed and green environmental protection. However, while the melting point of PTT is reduced by copolymerization modification, the glass transition temperature of PTT is also reduced, and the heat resistance of PTT is reduced. Since the front process of the squeeze roller in the production process is mostly high-temperature passivation treatment, the working temperature of the squeeze roller is usually above 70°C. Some squeeze rollers also have their own thermal conductive layer to improve the drying effect, which requires the material for preparing the non-woven roller to have a certain high temperature resistance.

[0004] The Chinese invention with application number 202010730323.1 discloses a high elastic nonwoven material for a squeeze roller and a preparation method, including an upper surface layer, an intermediate layer and a lower surface layer, wherein the upper surface layer and the lower surface layer are composed of the following raw material components according to mass percentage: 70%-90% PTT fiber, 10%-30% ES fiber, and the sum of the two raw materials is 100%; the intermediate layer is 100% PTT fiber. The Chinese invention with application number 202010816166.6 discloses a method for manufacturing a highly acid-resistant and alkali-resistant nonwoven material for a squeeze roller, firstly weighing according to mass percentage: 70%-90% high-strength polypropylene fiber, 10%-30% ultra-high molecular weight polyethylene fiber; mixing the high-strength polypropylene fiber with the ultra-high molecular weight polyethylene fiber to form a mixed fiber; and preparing a highly acid-resistant and alkali-resistant nonwoven material for a squeeze roller. Although the above two inventions solve the problems of poor acid and alkali resistance and low strength of the non-woven squeeze roller in the prior art, the heat resistance is poor and needs to be improved.

[0005] Therefore, preparing a nonwoven fabric with good resilience and heat resistance has great market potential. Summary of the invention

[0006] The purpose of the present invention is to overcome the problem in the prior art that while modifying the polyester to lower the melting point, its glass transition temperature will be lowered, thereby reducing the heat resistance, and to provide a polyester, a non-woven fabric and a preparation method thereof. The polyester has a lower melting point and a higher heat deformation temperature, and has good heat resistance.

[0007] In order to achieve the above object, the first aspect of the present invention provides a polyester having a melting point of 158-205° C. and a heat deformation temperature of 48-78° C. under a pressure of 0.45 MPa.

[0008] A second aspect of the present invention provides a method for preparing polyester, the method comprising the following steps:

[0009] (1) under esterification reaction conditions, a dibasic acid monomer, a diol monomer, a modified monomer and a catalyst are mixed to carry out a first stage reaction to obtain a prepolymer;

[0010] The modified monomer contains a monomer having a structure represented by formula (I) and a monomer having a structure represented by formula (II);

[0011]

[0012] Wherein, n is an integer from 4 to 10, R 1 , R 2 , R 3 and R 4 Each is independently selected from hydrogen or C1-C4 alkyl;

[0013] (2) Under polycondensation conditions, the prepolymer is subjected to a second stage reaction.

[0014] The third aspect of the present invention provides a nonwoven fabric, which is prepared using the polyester described in the first aspect and / or the polyester obtained by the preparation method described in the second aspect.

[0015] Through the above technical solution, the beneficial effects of the present invention are:

[0016] The polyester provided by the present invention has a low melting point and a high heat deformation temperature, good heat resistance, and has significant market prospects and environmental benefits. The preparation method of the polyester provided by the present invention modifies the polyester by using a monomer having a structure shown in formula (I) and a monomer having a structure shown in formula (II), so that the prepared polyester can have a relatively low melting point and significantly improve its heat deformation temperature, and has good heat resistance.

[0017] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0018] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0019] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0020] During the research process, the inventors of the present invention unexpectedly discovered that adding a monomer having a structure shown in formula (I) and a monomer having a structure shown in formula (II) during the preparation of polyester can effectively reduce the melting point of polyester while avoiding a decrease in the thermal deformation temperature, thereby improving its heat resistance. The polyester can be used to prepare a non-woven fabric with good resilience and heat resistance, and the non-woven fabric material can be used as a raw material for preparing a non-woven fabric squeezing roller.

[0021] The first aspect of the present invention provides a polyester having a melting point of 158-205° C. and a heat deformation temperature of 48-78° C. under a pressure of 0.45 MPa.

[0022] In the present invention, the melting point is measured by a Perkin-Elmer DSC-7 differential scanning calorimeter from PE Company. The heat deformation temperature is obtained by testing the sample with a load of 0.45 MPa according to "GB / T1634.2-2004 Determination of load deformation temperature Part 2: Plastics, hard rubber and long fiber reinforced composite materials".

[0023] The polyester provided by the present invention has a specific melting point and heat deformation temperature. It has a low melting point and a high heat deformation temperature, and has good heat resistance. When used in the preparation of non-woven fabrics, it can be directly hot-rolled and formed without the need for additional compounding of other fibers or adding adhesives. It has the advantages of being convenient, fast, green and environmentally friendly.

[0024] According to the present invention, preferably, the melting point of the polyester is 169-200°C, and the heat deformation temperature is 62-78°C under a pressure of 0.45 MPa.

[0025] In order to realize the use of the polyester provided by the present invention for preparing nonwoven fabrics, the polyester should have a high strength in addition to having a specific melting point and heat deformation temperature. Preferably, the viscosity of the polyester is 0.7-1.0 dL / g, and the strength of the polyester with this viscosity is better than that of low-viscosity polyester.

[0026] In the present invention, the viscosity of the polyester is tested according to "GB / T14189-2008 Fiber-grade polyester chips".

[0027] According to the present invention, preferably, the polyester contains a structural unit (A) represented by formula (I) and a structural unit (B) represented by formula (II);

[0028]

[0029] Wherein, n is an integer from 4 to 10, R 1 , R 2 , R 3 and R 4 Each is independently selected from hydrogen or a C1-C4 alkyl group. The inventors have found that, under this preferred embodiment, the polyester having the structural unit (A) and the structural unit (B) can increase the heat deformation temperature while lowering the melting point, and has good heat resistance.

[0030] In the present invention, in the monomer having the structure shown in formula (I), n can be 4, 5, 6, 7, 8, 9 or 10; in the monomer having the structure shown in formula (II), R 1 , R 2 , R 3 and R 4They may independently be hydrogen, hydroxyl, straight-chain alkyl or cycloalkyl, specifically methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, tert-butyl or other feasible C1-C4 alkyl.

[0031] According to the present invention, preferably, in the polyester, the content of the structural unit (A) is 1-12% by weight, specifically 1% by weight, 6% by weight, 12% by weight, or any value between the two aforementioned values; the content of the structural unit (B) is 5-40% by weight, specifically 5% by weight, 20% by weight, 40% by weight, or any value between the two aforementioned values. It should be noted that the content of the structural unit (A) is 1-12% by weight, which means that the content of the structural unit (A) in the polyester accounts for 1-12% of the total mass of the polyester; the content of the structural unit (B) is 5-40% by weight, which means that the content of the structural unit (B) in the polyester accounts for 5-40% of the total mass of the polyester.

[0032] According to the present invention, preferably, the polyester contains metal elements.

[0033] According to the present invention, preferably, the metal element is antimony and / or titanium.

[0034] According to the present invention, preferably, in the polyester, the content of the metal element is 0.01-0.04 wt %, specifically 0.01 wt %, 0.02 wt %, 0.03 wt %, 0.04 wt %, or any value between the foregoing two values.

[0035] A second aspect of the present invention provides a method for preparing polyester, the method comprising the following steps:

[0036] (1) under esterification reaction conditions, a dibasic acid monomer, a diol monomer, a modified monomer and a catalyst are mixed to carry out a first stage reaction to obtain a prepolymer;

[0037] The modified monomer contains a monomer having a structure represented by formula (I) and a monomer having a structure represented by formula (II);

[0038]

[0039] Wherein, n is an integer from 4 to 10, R 1 , R 2 , R 3 and R 4 Each is independently selected from hydrogen or C1-C4 alkyl;

[0040] (2) Under polycondensation conditions, the prepolymer is subjected to a second stage reaction.

[0041] The polyester preparation method provided by the present invention is simple and suitable for industrial production. The present invention reduces the melting point of the polyester and increases its heat deformation temperature through the synergistic effect between the monomer having the structure shown in formula (II) and the monomer having the structure shown in formula (I), thereby improving the heat resistance.

[0042] In the present invention, in the monomer having the structure represented by formula (I), n may be 4, 5, 6, 7, 8, 9 or 10.

[0043] According to the present invention, specifically, the monomer having the structure shown in formula (I) is a compound shown in formula (III);

[0044]

[0045] Here, x is an integer from 3 to 9.

[0046] In the monomer having the structure shown in formula (II) of the present invention, R 1 , R 2 , R 3 and R 4 They may independently be hydrogen, hydroxyl, straight-chain alkyl or cycloalkyl, specifically methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, tert-butyl or other feasible C1-C4 alkyl.

[0047] According to the present invention, preferably, R 1 , R 2 , R 3 and R 4 All of them can be hydrogen. Specifically, the monomer having the structure represented by formula (II) is preferably isophthalic acid.

[0048] According to the present invention, in order to further enable the polyester to increase the heat deformation temperature while lowering the melting point, preferably, the weight ratio of the monomer having the structure represented by formula (II) to the monomer having the structure represented by formula (I) is 0.4-8:1, specifically 0.4:1, 2:1, 4:1, 6:1, 8:1, or any value between the above two values.

[0049] According to the present invention, preferably, the dibasic acid monomer is an aromatic dibasic acid and is different from the monomer having the structure represented by formula (II), more preferably at least one of terephthalic acid, 4,4'-biphenyl dicarboxylic acid and 2,6-naphthalene dicarboxylic acid, and further preferably terephthalic acid.

[0050] According to the present invention, the diol monomer may be any diol. Preferably, the diol monomer is ethylene glycol and / or propylene glycol, more preferably propylene glycol, specifically 1,2-propylene glycol or 1,3-propylene glycol.

[0051] According to the present invention, in order to further reduce the melting point of polyester and increase its heat deformation temperature, preferably, the weight ratio of the dicarboxylic acid monomer, the diol monomer and the modifying monomer is 0.5-1.2:1:0.2-0.8.

[0052] According to the present invention, preferably, the catalyst contains an antimony catalyst and / or a titanium catalyst. The catalyst may contain an antimony catalyst, a titanium catalyst, or both. The inventors have found that under this preferred embodiment, the melting point of the polyester can be further reduced while its heat deformation temperature is increased, and the heat resistance is further improved.

[0053] According to the present invention, there is no particular limitation on the types of antimony-based catalysts and titanium-based catalysts. In order to further reduce the melting point of polyester while increasing its heat deformation temperature, preferably, the antimony-based catalyst is selected from at least one of ethylene glycol antimony, antimony trioxide and antimony acetate, more preferably ethylene glycol antimony; the titanium-based catalyst is tetrabutyl titanate and / or ethylene glycol titanium, more preferably tetrabutyl titanate.

[0054] In the present invention, the content of the catalyst can be selected according to the performance requirements of the polyester. Preferably, relative to 1000g of the dibasic acid monomer, the added amount of the catalyst is 0.5-1.5g, specifically 0.5g, 1.0g, 1.5g, or any value between the above two values.

[0055] In the present invention, the above-mentioned dibasic acid monomer, diol monomer, modified monomer and catalyst can be obtained commercially, or can be prepared by the preparation method disclosed in the prior art.

[0056] According to the present invention, in order to further improve the reaction rate and product yield of the first stage reaction, preferably, the conditions of the esterification reaction at least include: isolation of oxygen, temperature of 230-250°C, specifically 230°C, 240°C, 250°C, or any value between the above two values; pressure of 0.18-0.22MPa, specifically 0.18MPa, 0.20MPa, 0.22MPa, or any value between the above two values. Isolation of oxygen can be achieved by filling the reaction system with an inert gas such as nitrogen or helium, specifically, the inert gas is nitrogen.

[0057] In the present invention, the first stage reaction is carried out under stirring conditions, and there is no particular limitation on the stirring rate, which can be determined by the experimenter according to the actual situation.

[0058] In the present invention, the experimenter can determine the conditions for the end of the first stage reaction according to the actual situation, for example, according to the amount of water in the product. Preferably, the conditions for the end of the first stage reaction process at least include: the water output of the product is not less than 90% of the theoretical water output.

[0059] According to the present invention, preferably, the conditions for the polycondensation reaction include at least: a temperature of 240-260°C, specifically 240°C, 250°C, 260°C, or any value between the foregoing two values; and a vacuum pressure of less than 100Pa.

[0060] In the present invention, the experimenter can determine the conditions for the end of the second stage reaction process according to the actual situation. Preferably, the conditions for the end of the second stage reaction process at least include: the stirring current reaches a preset value. The inventors found that under this preferred specific embodiment, the product of the esterification reaction has a better polycondensation effect, and improves the stability of the structure and performance of the polyester.

[0061] It should be noted that the preset value of the stirring current in the present invention is the rated current value of the reactor used. Different reactors have different rated current values.

[0062] According to the present invention, before reaching the polycondensation reaction conditions, the reaction system needs to be gradually heated up, and the heating rate may be 0.2-1.4° C. / min.

[0063] The third aspect of the present invention provides a nonwoven fabric, which is prepared using the polyester described in the first aspect and / or the polyester obtained by the preparation method described in the second aspect.

[0064] In the present invention, the non-woven fabric can be prepared from polyester by a conventional preparation method. Specifically, the preparation process of the non-woven fabric includes: preparing polyester into polyester fibers, and preparing the non-woven fabric through opening and laying, needle punching, and hot rolling.

[0065] According to the present invention, the nonwoven fabric has a thickness of 0.5 mm and a density of 200 g / m 2 Preferably, the transverse breaking strength of the nonwoven fabric is greater than 63N / 5cm, and the longitudinal breaking strength is greater than 70N / 5cm; the transverse breaking elongation of the nonwoven fabric is greater than 150%, and the longitudinal breaking elongation is greater than 105%.

[0066] According to the present invention, the nonwoven fabric has a thickness of 0.5 mm and a density of 200 g / m 2 Preferably, the elastic recovery rate of the nonwoven fabric under a strain of 50% is greater than 84%.

[0067] The present invention is tested according to GB / T3923.1-2013 Tensile properties of textile fabrics Part 1: Determination of breaking strength and breaking elongation, and the elastic recovery rate of the non-woven fabric is tested under a certain load condition.

[0068] In the present invention, the nonwoven fabric has a low melting point and can also improve its heat deformation temperature, has good heat resistance, and has good strength and resilience. It has good application in the preparation of a squeeze roller. When the squeeze roller is in close contact with a metal plate strip, a better squeezing effect can be obtained, which can solve the problem of metal plate strip slippage.

[0069] According to a particularly preferred embodiment of the present invention, a method for preparing a nonwoven fabric is provided, comprising the following steps:

[0070] (1) mixing a dibasic acid monomer, a diol monomer, a modified monomer and a catalyst, and conducting an esterification reaction under a nitrogen atmosphere at a temperature of 230-250° C. and a pressure of 0.18-0.22 MPa until the water output in the esterification reaction product is not less than 90% of the theoretical water output;

[0071] The modified monomer contains isophthalic acid and a compound represented by formula (III);

[0072]

[0073] Wherein, x is an integer of 3-9; the dibasic acid monomer is terephthalic acid, the diol monomer is propylene glycol; the weight ratio of isophthalic acid to the compound represented by formula (III) is 0.4-8:1; the weight ratio of the dibasic acid monomer, the diol monomer and the modified monomer is 0.5-1.2:1:0.2-0.8; the catalyst is antimony ethylene glycol and / or tetrabutyl titanate; relative to 1000g of the dibasic acid monomer, the weight of the catalyst is 0.5-1.5g;

[0074] (2) the product of the esterification reaction in step (1) is heated under reduced pressure for 45 minutes to a temperature of 240-260° C. and a vacuum pressure of less than 100 Pa, entering a high vacuum polycondensation stage, and discharging the product when the stirring current reaches the rated current value to obtain polyester;

[0075] (3) The polyester obtained in step (2) is prepared into polyester fiber, and then the fiber is opened, laid, needled, and hot-rolled to prepare a non-woven fabric.

[0076] In the above preferred embodiment, the prepared nonwoven fabric has a relatively low melting point and can improve its heat deformation temperature, has good heat resistance, and also has good strength and resilience, and has significant market prospects and environmental benefits.

[0077] The present invention is described in detail below with reference to the embodiments, but the scope of the present invention is not limited thereby.

[0078] In the following examples and comparative examples, all the raw materials used were commercially available.

[0079] The melting point is tested using a differential scanning calorimeter.

[0080] The heat deformation temperature is tested on the sample with a load of 0.45 MPa in accordance with GB / T1634.2-2004 Determination of load deformation temperature Part 2: Plastics, hard rubber and long fiber reinforced composite materials.

[0081] The viscosity is tested according to GB / T14189-2008 Fiber-grade polyester chips.

[0082] The transverse breaking strength, longitudinal breaking strength, transverse breaking elongation, longitudinal breaking elongation and elastic recovery rate are tested in accordance with "GB / T3923.1-2013 Tensile properties of textile fabrics Part 1: Determination of breaking strength and breaking elongation".

[0083] Example 1

[0084] In a 20L polymerization kettle, 4.38kg of terephthalic acid, 4.12kg of 1,3-propylene glycol, 0.62kg of isophthalic acid, 558g of a compound represented by formula (III) (x is 6), 3.32g of antimony glycol and 2.12g of tetrabutyl titanate were added as raw materials and stirred into a uniform slurry, and then added to a reactor for esterification reaction; the esterification reaction was carried out under pressure in a nitrogen atmosphere, the pressure was controlled at 0.18MPa, the temperature was controlled at 250°C, and the esterification water distillation amount reached more than 90% of the theoretical value, which was regarded as the end point of the esterification reaction; after the esterification reaction was completed, the temperature was gradually increased to enter a low vacuum stage, and after a low vacuum time of about 45min, a high vacuum polycondensation stage was entered, and the vacuum pressure was less than 100Pa), the polycondensation temperature was 260°C, and the material was discharged when the stirring current of the reactor reached a set value to obtain polyester; after the polyester was prepared into polyester fiber, a non-woven fabric was prepared through opening, laying, needle punching and hot rolling.

[0085] Example 2

[0086] In a 20L polymerization kettle, 3.88kg of terephthalic acid, 4.12kg of 1,3-propylene glycol, 1.12kg of isophthalic acid, 248g of a compound represented by formula (III) (x is 3), 1.62g of antimony glycol and 1.32g of tetrabutyl titanate were added as raw materials and stirred into a uniform slurry, and then added to a reactor for esterification reaction; the esterification reaction was carried out under pressure in a nitrogen atmosphere, the pressure was controlled at 0.2MPa, the temperature was controlled at 240°C, and the esterification water distillation amount reached more than 90% of the theoretical value, which was regarded as the end point of the esterification reaction; after the esterification reaction was completed, the temperature was gradually increased to enter a low vacuum stage, and after a low vacuum time of about 45min, a high vacuum polycondensation stage was entered, the vacuum pressure was less than 100Pa, the polycondensation temperature was 255°C, and the material was discharged when the stirring current of the reactor reached a set value to obtain polyester; after the polyester was prepared into polyester fiber, a non-woven fabric was prepared through opening, laying, needle punching and hot rolling.

[0087] Example 3

[0088] In a 20L polymerization kettle, 2.52kg of terephthalic acid, 4.12kg of 1,3-propylene glycol, 2.48kg of isophthalic acid, 310g of a compound represented by formula (III) (x is 3), 1.62g of antimony glycol and 1.32g of tetrabutyl titanate were added as raw materials and stirred into a uniform slurry, and then added to a reactor for esterification reaction; the esterification reaction was carried out under pressure in a nitrogen atmosphere, the pressure was controlled at 0.2MPa, the temperature was controlled at 250°C, and the esterification water distillation amount reached more than 90% of the theoretical value, which was regarded as the end point of the esterification reaction; after the esterification reaction was completed, the temperature was gradually increased to enter a low vacuum stage, and after a low vacuum time of about 45min, a high vacuum polycondensation stage was entered, the vacuum pressure was less than 100Pa, the polycondensation temperature was 255°C, and the material was discharged when the stirring current of the reactor reached a set value to obtain polyester; after the polyester was prepared into polyester fiber, a non-woven fabric was prepared through opening, laying, needle punching and hot rolling.

[0089] Example 4

[0090] In a 20L polymerization kettle, 3.45kg of terephthalic acid, 4.12kg of 1,3-propylene glycol, 1.55kg of isophthalic acid, 745g of a compound represented by formula (III) (x is 3), 1.62g of antimony glycol and 1.32g of tetrabutyl titanate were added as raw materials and stirred into a uniform slurry, and then added to a reactor for esterification reaction; the esterification reaction was carried out under pressure in a nitrogen atmosphere, the pressure was controlled at 0.2MPa, the temperature was controlled at 240°C, and the esterification water distillation amount reached more than 90% of the theoretical value, which was regarded as the end point of the esterification reaction; after the esterification reaction was completed, the temperature was gradually increased to enter a low vacuum stage, and after a low vacuum time of about 45min, a high vacuum polycondensation stage was entered, the vacuum pressure was less than 100Pa, the polycondensation temperature was 250°C, and the material was discharged when the stirring current of the reactor reached a set value to obtain polyester; after the polyester was prepared into polyester fiber, a non-woven fabric was prepared through opening, laying, needle punching and hot rolling.

[0091] Example 5

[0092] In a 20L polymerization kettle, 4.68kg of terephthalic acid, 4.12kg of 1,3-propylene glycol, 0.32kg of isophthalic acid, 745g of a compound represented by formula (III) (x is 3), 1.62g of antimony glycol and 1.32g of tetrabutyl titanate were added as raw materials and stirred into a uniform slurry, and then added to a reactor for esterification reaction; the esterification reaction was carried out under pressure in a nitrogen atmosphere, the pressure was controlled at 0.2MPa, the temperature was controlled at 250°C, and the esterification water distillation amount reached more than 90% of the theoretical value, which was regarded as the end point of the esterification reaction; after the esterification reaction was completed, the temperature was gradually increased to enter a low vacuum stage, and after a low vacuum time of about 45min, a high vacuum polycondensation stage was entered, the vacuum pressure was less than 100Pa, the polycondensation temperature was 260°C, and the material was discharged when the stirring current of the reactor reached a set value to obtain polyester; after the polyester was prepared into polyester fiber, a non-woven fabric was prepared through opening, laying, needle punching and hot rolling.

[0093] Example 6

[0094] In a 20L polymerization kettle, 3.45kg of terephthalic acid, 4.12kg of 1,3-propylene glycol, 1.55kg of isophthalic acid, 745g of a compound represented by formula (III) (x is 3), 3.32g of antimony glycol and 1.32g of tetrabutyl titanate were added as raw materials and stirred into a uniform slurry, and then added to a reactor for esterification reaction; the esterification reaction was carried out under pressure in a nitrogen atmosphere, the pressure was controlled at 0.2MPa, the temperature was controlled at 240°C, and the esterification water distillation amount reached more than 90% of the theoretical value, which was regarded as the end point of the esterification reaction; after the esterification reaction was completed, the temperature was gradually increased to enter a low vacuum stage, and after a low vacuum time of about 45min, a high vacuum polycondensation stage was entered, the vacuum pressure was less than 100Pa, the polycondensation temperature was 255°C, and the material was discharged when the stirring current of the reactor reached a set value to obtain polyester; after the polyester was prepared into polyester fiber, a non-woven fabric was prepared through opening, laying, needle punching and hot rolling.

[0095] Example 7

[0096] In a 20L polymerization kettle, 3.45kg of terephthalic acid, 4.12kg of 1,3-propylene glycol, 1.55kg of isophthalic acid, 745g of a compound represented by formula (III) (x is 3), and 2.94g of ethylene glycol antimony are added as raw materials and stirred into a uniform slurry, and then added to a reactor for esterification reaction; the esterification reaction is carried out under pressure in a nitrogen atmosphere, the pressure is controlled at 0.2MPa, the temperature is controlled at 230°C, and the esterification water distillation amount reaches more than 90% of the theoretical value, which is regarded as the end point of the esterification reaction; after the esterification reaction is completed, the temperature is gradually increased to enter a low vacuum stage, and after a low vacuum time of about 45min, a high vacuum polycondensation stage is entered, the vacuum pressure is less than 100Pa, the polycondensation temperature is 240°C, and the material is discharged when the stirring current of the reactor reaches the set value to obtain polyester; after the polyester is prepared into polyester fiber, a non-woven fabric is prepared through opening, laying, needle punching, and hot rolling.

[0097] Example 8

[0098] In a 20L polymerization kettle, 3.76kg of terephthalic acid, 4.12kg of 1,3-propylene glycol, 1.24kg of isophthalic acid, 62g of a compound represented by formula (III) (x is 3), 1.62g of antimony ethylene glycol and 1.32g of tetrabutyl titanate were added as raw materials and stirred into a uniform slurry, and then added into a reactor for esterification reaction; the esterification reaction was carried out under pressure in a nitrogen atmosphere, the pressure was controlled at 0.2MPa, the temperature was controlled at 240°C, and the esterification water distillation amount reached more than 90% of the theoretical value, which was regarded as the end point of the esterification reaction; after the esterification reaction was completed, the temperature was gradually increased to enter a low vacuum stage, and after a low vacuum time of about 45min, a high vacuum polycondensation stage was entered, the vacuum pressure was less than 100Pa, the polycondensation temperature was 255°C, and the material was discharged when the stirring current of the reactor reached a set value to obtain polyester; after the polyester was prepared into polyester fiber, a non-woven fabric was prepared through opening, laying, needle punching and hot rolling.

[0099] Example 9

[0100] In a 20L polymerization kettle, 2.83kg of terephthalic acid, 4.12kg of 1,3-propylene glycol, 2.17kg of isophthalic acid, 186g of a compound represented by formula (III) (x is 9), 1.12g of antimony glycol and 1.12g of tetrabutyl titanate were added as raw materials and stirred into a uniform slurry, and then added to a reactor for esterification reaction; the esterification reaction was carried out under pressure in a nitrogen atmosphere, the pressure was controlled at 0.22MPa, the temperature was controlled at 240°C, and the esterification water distillation amount reached more than 90% of the theoretical value, which was regarded as the end point of the esterification reaction; after the esterification reaction was completed, the temperature was gradually increased to enter a low vacuum stage, and after a low vacuum time of about 45min, a high vacuum polycondensation stage was entered, the vacuum pressure was less than 100Pa, the polycondensation temperature was 260°C, and the material was discharged when the stirring current of the reactor reached a set value to obtain polyester; after the polyester was prepared into polyester fiber, a non-woven fabric was prepared through opening, laying, needle punching and hot rolling.

[0101] Example 10

[0102] In a 20L polymerization kettle, 4.38kg of 4,4-biphenyldicarboxylic acid, 4.12kg of ethylene glycol, 0.62kg of isophthalic acid, 558g of a compound represented by formula (III) (x is 6), 3.32g of antimony glycol and 2.12g of tetrabutyl titanate were added as raw materials and stirred into a uniform slurry, and then added to a reactor for esterification reaction; the esterification reaction was carried out under pressure in a nitrogen atmosphere, the pressure was controlled at 0.18MPa, the temperature was controlled at 250°C, and the esterification water distillation amount reached more than 90% of the theoretical value, which was regarded as the end point of the esterification reaction; after the esterification reaction was completed, the temperature was gradually increased to enter a low vacuum stage, and after a low vacuum time of about 45min, a high vacuum polycondensation stage was entered, and the vacuum pressure was less than 100Pa), the polycondensation temperature was 255°C, and the material was discharged when the stirring current of the reactor reached a set value to obtain polyester; after the polyester was prepared into polyester fiber, a non-woven fabric was prepared through opening, laying, needle punching and hot rolling.

[0103] Comparative Example 1

[0104] In a 20L polymerization kettle, 5kg of terephthalic acid, 4.12kg of 1,3-propylene glycol, 558g of a compound represented by formula (III) (x is 6), 3.32g of antimony glycol and 2.12g of tetrabutyl titanate are added as raw materials and stirred into a uniform slurry, and then added into a reactor for esterification reaction; the esterification reaction is carried out under pressure in a nitrogen atmosphere, the pressure is controlled at 0.18MPa, the temperature is controlled at 245°C, and the esterification water distillation amount reaches more than 90% of the theoretical value, which is regarded as the end point of the esterification reaction; after the esterification reaction is completed, the temperature is gradually increased to enter a low vacuum stage, and after a low vacuum time of about 45min, a high vacuum polycondensation stage is entered, and the vacuum pressure is less than 100Pa), the polycondensation temperature is 255°C, and the material is discharged when the stirring current of the reactor reaches the set value to obtain polyester; after the polyester is prepared into polyester fiber, a non-woven fabric is prepared through opening, laying, needle punching and hot rolling.

[0105] Comparative Example 2

[0106] In a 20L polymerization kettle, 3.76kg of terephthalic acid, 4.12kg of 1,3-propylene glycol, 1.24kg of isophthalic acid, 1.62g of antimony glycol and 1.32g of tetrabutyl titanate were added as raw materials and stirred into a uniform slurry, and then added to a reactor for esterification reaction; the esterification reaction was carried out under pressure in a nitrogen atmosphere, the pressure was controlled at 0.2MPa, the temperature was controlled at 230°C, and the esterification water distillation amount reached more than 90% of the theoretical value, which was regarded as the end point of the esterification reaction; after the esterification reaction was completed, the temperature was gradually increased to enter the low vacuum stage, and after the low vacuum time was about 45min, it entered the high vacuum polycondensation stage, the vacuum pressure was less than 100Pa, the polycondensation temperature was 260°C, and the material was discharged when the stirring current of the reactor reached the set value to obtain polyester; after the polyester was prepared into polyester fiber, the non-woven fabric was prepared through opening, laying, needle punching and hot rolling.

[0107] Comparative Example 3

[0108] In a 20L polymerization kettle, 5kg of terephthalic acid, 4.12kg of 1,3-propylene glycol, 1.62g of antimony ethylene glycol and 1.32g of tetrabutyl titanate are added as raw materials and stirred into a uniform slurry, and then added into a reactor for esterification reaction; the esterification reaction is carried out under pressure in a nitrogen atmosphere, the pressure is controlled at 0.2MPa, the temperature is controlled at 230°C, and the esterification water distillation amount reaches more than 90% of the theoretical value, which is regarded as the end point of the esterification reaction; after the esterification reaction is completed, the temperature is gradually increased to enter a low vacuum stage, and after a low vacuum time of about 45 minutes, it enters a high vacuum polycondensation stage, the vacuum pressure is less than 100Pa, the polycondensation temperature is 255°C, and the material is discharged when the stirring current of the reactor reaches the set value to obtain polyester; after the polyester is prepared into polyester fiber, the non-woven fabric is prepared through opening, laying, needle punching and hot rolling.

[0109] Test Example 1

[0110] The polyesters prepared in Examples 1 to 10 and Comparative Examples 1 to 3 were tested for the contents of structural unit (A), structural unit (B), antimony and titanium. The contents of structural unit (A) and structural unit (B) were tested using a gas chromatograph, and the contents of antimony and titanium were tested using an inductively coupled plasma (ICP) spectrometer. The results are shown in Table 1.

[0111] Table 1

[0112]

[0113]

[0114] Test Example 2

[0115] The viscosity, melting point and heat deformation temperature of the polyesters prepared in Examples 1 to 10 and Comparative Examples 1 to 3 were measured. The results are shown in Table 2.

[0116] Table 2

[0117] serial number Viscosity (dL / g) Melting point(℃) Heat deformation temperature(℃) Example 1 0.854 198 75 Example 2 0.899 188 62 Example 3 0.917 158 66 Example 4 0.903 173 78 Example 5 0.925 200 70 Example 6 0.810 169 74 Example 7 0.922 172 72 Example 8 0.878 181 48 Example 9 0.921 165 55 Example 10 0.915 205 60 Comparative Example 1 0.889 218 66 Comparative Example 2 0.869 189 43 Comparative Example 3 0.902 220 40

[0118] It can be seen from the results in Table 2 that, compared with Comparative Examples 1 to 3, the polyesters prepared in Examples 1 to 10 have a low melting point and can increase their heat deformation temperature, thus having good heat resistance.

[0119] Test Example 3

[0120] The polypropylene nonwoven fabric (commercially available), the nonwoven fabrics prepared in Examples 1 to 10 and Comparative Examples 1 to 3 were made into a nonwoven fabric having a thickness of 0.5 mm and a density of 200 g / m 2 The samples were prepared and their strength and elastic recovery were tested. The results are shown in Table 3.

[0121] Table 3

[0122]

[0123] It can be seen from the results in Table 3 that, compared with the polypropylene non-woven fabric, the non-woven fabrics prepared in Examples 1 to 10 have good strength and resilience.

[0124] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A polyester, characterized in that The melting point of the polyester is 158-205° C., and the heat deformation temperature is 48-78° C. under a pressure of 0.45 MPa.

2. The polyester according to claim 1, characterized in that The melting point of the polyester is 169-200°C, and the heat deformation temperature is 62-78°C under a pressure of 0.45 MPa; Preferably, the viscosity of the polyester is 0.7-1.0 dL / g.

3. The polyester according to claim 1 or 2, characterized in that The polyester contains a structural unit (A) represented by formula (I) and a structural unit (B) represented by formula (II); Wherein, n is an integer of 4-10, and R1, R2, R3 and R4 are each independently selected from hydrogen or a C1-C4 alkyl group; Preferably, in the polyester, the content of the structural unit (A) is 1-12% by weight, and the content of the structural unit (B) is 5-40% by weight.

4. The polyester according to claim 1 or 2, characterized in that The polyester contains metal elements; Preferably, the metal element is antimony and / or titanium; Preferably, in the polyester, the content of the metal element is 0.01-0.04 wt %.

5. A method for preparing polyester, characterized in that: The method comprises the following steps: (1) under esterification reaction conditions, a dibasic acid monomer, a diol monomer, a modified monomer and a catalyst are mixed to carry out a first stage reaction to obtain a prepolymer; The modified monomer contains a monomer having a structure represented by formula (I) and a monomer having a structure represented by formula (II); Wherein, n is an integer of 4-10, and R1, R2, R3 and R4 are each independently selected from hydrogen or a C1-C4 alkyl group; (2) Under polycondensation conditions, the prepolymer is subjected to a second stage reaction.

6. The preparation method according to claim 5, characterized in that: The weight ratio of the monomer having the structure represented by formula (II) to the monomer having the structure represented by formula (I) is 0.4-8:1; Preferably, the monomer having the structure represented by formula (II) is isophthalic acid, and the dibasic acid monomer is an aromatic dibasic acid and is different from the monomer having the structure represented by formula (II), more preferably at least one of terephthalic acid, 4,4'-biphenyl dicarboxylic acid and 2,6-naphthalene dicarboxylic acid; Preferably, the diol monomer is ethylene glycol and / or propylene glycol, more preferably propylene glycol; Preferably, the weight ratio of the dibasic acid monomer, the diol monomer and the modifying monomer is 0.5-1.2:1:0.2-0.

8.

7. The preparation method according to claim 5, characterized in that: The catalyst contains an antimony-based catalyst and / or a titanium-based catalyst; Preferably, the antimony-based catalyst is selected from at least one of antimony glycolate, antimony trioxide and antimony acetate, more preferably antimony glycolate; the titanium-based catalyst is tetrabutyl titanate and / or titanium glycolate, more preferably tetrabutyl titanate.

8. The preparation method according to any one of claims 5 to 7, characterized in that: In step (1), the conditions of the esterification reaction include at least: a temperature of 230-250° C. and a pressure of 0.18-0.22 MPa; Preferably, in step (2), the conditions for the polycondensation reaction include at least: a temperature of 240-260° C. and a vacuum pressure of less than 100 Pa.

9. A nonwoven fabric, characterized in that: The polyester is prepared by using the polyester described in any one of claims 1 to 4 and / or the polyester obtained by the preparation method described in any one of claims 5 to 8.

10. The nonwoven fabric according to claim 9, characterized in that The transverse breaking strength of the non-woven fabric is greater than 63N / 5cm, and the longitudinal breaking strength is greater than 70N / 5cm; the transverse breaking elongation of the non-woven fabric is greater than 150%, and the longitudinal breaking elongation is greater than 105%; Preferably, the elastic recovery rate of the nonwoven fabric under a 50% strain condition is greater than 84%.

Citation Information

Patent Citations

  • A high-elasticity nonwoven material for squeeze rollers and its preparation method

    CN111945292B

  • Manufacturing method of high-acid-base-resistance non-woven material for wringing roller

    CN112080854A

  • Preparation method of phenolic resin modified water-based saturated polyester resin

    CN103865050A

  • Waterborne impregnating insulation varnish capable of being quickly cured at low temperature and preparation method thereof

    CN104194581A

  • Polyester resin with excellent yellowing resistance for powder coating and preparation method of polyester resin

    CN114316227A